Innovations in Practice: Effectiveness of specialist adolescent outreach service for at‐risk adolescents. Issue 2 (16th March 2012) - Chia, Andrew; Assan, Ben; Finch, Erin; Stargatt, Robyn; Burchell, Peter; Jones, Hayden; Heywood‐Smith, Jane
<x xml:space="preserve">Abstract</x> Background Outcomes are reported for an assertive outreach team for adolescents that combines flexible service delivery (e.g. outreach) and broad‐ranging interventions. Method A retrospective evaluation over a 2‐year period from 30 June 2006 to 30 June 2008 examined rates of hospitalisation, engagement with education and scores on the Child Global Assessment Scale (CGAS). Results The sample showed statistically significant decreases in hospitalisation rates (from 47% to 17%) and increases in engagement with education (full‐time attendance from 23% to 56%). There was a mean increase of 7.4 points on the CGAS. Conclusion An intensive, flexible and broad‐ranging approach can be applied to adolescents who display at‐risk behaviours and/or have high risk factors for poor long‐term outcome.